Kualitas Kesehatan Pasien Tuberkulosis di Rumah Sakit Wava Husada Malang - Rudy Mardianto; Erika Sastya Intan; Ratih Tyas Widara (Pusat riset dan Inovasi Nasional, 2025)
Tuberculosis (TB) is an infectious disease that remains a global and national health problem, with Indonesia among the top three countries with the highest TB burden in the world. Long TB treatment often impacts the physical, social, emotional, functional, and spiritual aspects of patients, so measuring the quality of health is important in assessing the success of therapy comprehensively. This study aims to determine the description of the quality of health of Tuberculosis patients at Wava Husada Hospital Malang using the Functional Assessment of Chronic Illness Therapy Tuberculosis (FACIT-TB) instrument. This study is a descriptive study with a cross-sectional approach conducted on outpatient TB patients at Wava Husada Hospital Malang during June–August 2025. A total of 113 respondents who met the inclusion criteria were included. Data were obtained through the FACIT-TB questionnaire, which comprises five main variables: Physical Well-Being, Social/Family Well-Being, Emotional Well-Being, Functional Well-Being, and Spiritual Well-Being. The results showed that the majority of patients (53.1%) experienced moderate physical impairment, 73.5% had good social engagement, and 70.8% were emotionally stable. Fifty-four percent of respondents still had moderate functional impairment, while 45.1% were in the moderate spiritual impairment category. These findings indicate that although most patients demonstrated good emotional and social adaptation, physical, functional, and spiritual challenges remain that require further attention in healthcare. In conclusion, the overall quality of health of TB patients at Wava Husada Hospital in Malang is in the moderate category. These results underscore the importance of a multidimensional approach to TB patient management, emphasizing not only medical aspects but also psychosocial and spiritual support to improve therapy success and patient quality of life.